2012
DOI: 10.1021/ic302328e
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Hydroxyacetate and Its Transformation to Nanocrystalline Zinc Oxide

Abstract: The synthesis of nanocrystalline ZnO by thermal decomposition of zinc hydroxyacetate, Zn(5)(OH)(8)(CH(3)CO(2))(2)·nH(2)O, was investigated. The decomposition process was examined using X-ray diffraction, thermogravimetric analysis, mass spectrometry, electron microscopy, Brunauer-Emmett-Teller surface area analysis, and solid-state NMR spectroscopy. Intermediate Zn(5)(OH)(8)(CH(3)CO(2))(2)·nH(2)O phases form at temperatures up to 110 °C from the starting compound Zn(5)(OH)(8)(CH(3)CO(2))(2)·2H(2)O by partial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 31 publications
9
88
1
Order By: Relevance
“…(1), because the hydroxide ions and zinc cations are consumed into the newly created zinc hydroxide acetate, which is the very first precipitation product under such conditions (Biswick et al 2009;Moezzi et al 2013). The thermodynamic analysis strongly supports the model of the reaction mechanism involving the primary precipitation of the layered zinc hydroxide acetates (Biswick et al 2009) against interpretations involving zinc hydroxide formation from zinc acetate (Wang et al 2005): …”
Section: Cellulosementioning
confidence: 57%
“…(1), because the hydroxide ions and zinc cations are consumed into the newly created zinc hydroxide acetate, which is the very first precipitation product under such conditions (Biswick et al 2009;Moezzi et al 2013). The thermodynamic analysis strongly supports the model of the reaction mechanism involving the primary precipitation of the layered zinc hydroxide acetates (Biswick et al 2009) against interpretations involving zinc hydroxide formation from zinc acetate (Wang et al 2005): …”
Section: Cellulosementioning
confidence: 57%
“…S1 †). 11 The greater mass loss of the non-oriented nanoparticle system (ZA-8g) in the low temperature region was due to the larger surface area (33.6 m 2 g À1 ) accessible for water sorption in this sample compared to the sample based on the densely packed oriented nanoparticles (ZN-8g) (12.6 m 2 g À1 ) ( Table 1). It was reported in another paper that only a few nanoparticles deviated from perfect alignment as a result of lattice imperfection, and improper stacking in contacting areas among the primary nanoparticles 44 inside the ower-shaped particles.…”
Section: Particle Characterisationmentioning
confidence: 92%
“…The nanoparticles doubled in size while the submicron particles decreased from ca. Moezzi et al 11 reported that acetone, acetic acid, acetic anhydride and water evaporated in three steps at high temperatures during the thermal decomposition of ZHS into ZnO. Mouzon et al 45 modelled the transient structure during sintering.…”
Section: Particle Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some works demonstrate the huge influence that ambient humidity 7 , precursor 8 or solvent 9 have on the pyrolysis of zinc acetate dihydrate (ZAD) and the subsequent formation of ZnO 10,11,12 . Other reports highlight the appearance of different intermediate compounds, such as hydroxyl-or anhydrous acetates 13 , oxo-acetates 14 or hydrated hydroxyl-acetates 15 when similar ZAD species degrade, giving rise to nanowires 16 , nanobelts 17 or other nanostructures 18,19,20 .…”
Section: Introductionmentioning
confidence: 99%